Second-Order Linear Differential Equations with Solutions in Analytic Function Spaces. (12th February 2019) - Long, Jianren; Sun, Yu; Zhang, Shimei; Hu, Guangming
Abstract : This research is concerned with second-order linear differential equationf ′ ′ + A ( z ) f = 0, whereA ( z ) is an analytic function in the unit disc. On the one hand, some sufficient conditions for the solutions to be inα -Bloch (littleα -Bloch) space are found by using exponential type weighted Bergman reproducing kernel formula. On the other hand, we find also some sufficient conditions for the solutions to be in analytic Morrey (little analytic Morrey) space by using the representation formula.